Pouchitis--recurrence of the inflammatory bowel disease? - Luukkonen, P (1994)
The incidence and characteristics of reservoir inflammation after restorative proctocolectomy for ulcerative colitis were studied in a series of 179 patients. The median follow up time was 27 months (range 6-80). Pouchitis occurred in 36 patients (20%) and nine of these (5%) developed a chronic, persisting pouchitis. There were no pouch failures as a result of pouchitis and no significant adverse effect on longterm functional outcome. The overall cumulative risk to develop pouchitis four years after surgery was 23%. The risk of pouchitis is unpredictable on clinical grounds except that there were significantly less patients with left sided colitis in the group who subsequently developed pouchitis. Morphological and histochemical studies showed a greater degree of colonic metaplasia in the pouch mucosa in patients with pouchitis and patients with a chronic pouchitis had the highest degree of changes. The results support the view that pouchitis is a novel manifestation of inflammatory bowel disease in ileal mucosa that has changed slowly to a colon like mucosa.